Environmental Geopolitics of Climate Engineering Proposals in the IPCC 5th Assessment Report - O'Lear, Shannon; Hane, Madisen K.; Neal, Abigail P.; Stallings, Lauren Louise M.; Wadood, Sierra; Park, Jimin (Frontiers in Climate, 2021)
Environmental geopolitics offers an analytical approach that considers how environmental themes are brought into the service of geopolitical agendas. Of particular concern are claims about environment-related security and risk and the justification of actions (or inactions) proposed to deal with those claims. Environmental geopolitical analysis focuses on geographical knowledge and how that knowledge is generated and applied to stabilize specific understandings of the world. Climate engineering is a realm in which certain kinds of geographical knowledge, in the form of scientific interpretations of environmental interactions, are utilized to support a selective agenda that, despite claims about benefiting people and environments on a global scale, may be shown to reinforce uneven relationships of power as well as patterns of injustice. This paper focuses on how the IPCC AR5 discusses and portrays climate engineering. This particular conversation is significant, since the IPCC is widely recognized as reflecting current, international science and understanding of climate change processes and possible responses. We demonstrate an initial, environmental geopolitical analysis of this portrayal and discussion around climate engineering proposals by observing how the role and meaning of environmental features is limited, how human agency and impact in these scenarios is selective, and how insufficient attention is paid to spatial dimensions and impacts of these proposals. This paper contributes to a larger conversation about why it matters how we engage in discussion about climate impacts and issues; a central argument is that it is vital that we consider these proposed plans in terms of what they aim to secure, for whom, how and where.